Coercive Bargaining and Communication Acts of Local Government in Foreign Direct Investment - Kaukab, M. Elfan (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2024)
This research will analyze how communication mechanism implemented by local government in conducting coercive bargaining with the foreign investors. It aims to describe the coercive bargaining mechanism and communication actions in the process of managing FDI in Indonesia. This research covers areas that lack academic research, namely the mechanism of coercive bargaining in FDI negotiations in the regions. By studying the mechanism of coercive bargaining, this research reveals the input side of FDI process in influencing people’s economy. This research also shows the considerations used in encouraging coercive bargaining and its relation with the bargaining power of the local government and investors.